2023
DOI: 10.1007/s10803-023-06064-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexual Victimization Among Autistic and Non-Autistic College Students

Abstract: Purpose. This study examined predictors of sexual victimization among autistic and non-autistic college students. Specifically, we aimed to determine whether autistic students are more likely than non-autistic students to experience unwanted sexual contact and sexual assault, controlling for co-occurring diagnoses. We also aimed to determine whether students with other disabilities, specifically ADHD, learning disability (LD), and psychological disorders, are more likely than students without these disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The third college sample was based on a smaller sample size of 540, half of whom were autistic. In this sample there was no significant group difference in reported rates of unwanted sexual contact or sexual assault (Libster et al, 2023). Griffiths et al (2019) surveyed 426 autistic adults (M = 44 years, SD = 14.37) and 268 non-autistic adults (M = 51 years, SD = 15.33) about a range of negative life experiences, including violence.…”
Section: Rates Of Interpersonal Violencementioning
confidence: 89%
See 3 more Smart Citations
“…The third college sample was based on a smaller sample size of 540, half of whom were autistic. In this sample there was no significant group difference in reported rates of unwanted sexual contact or sexual assault (Libster et al, 2023). Griffiths et al (2019) surveyed 426 autistic adults (M = 44 years, SD = 14.37) and 268 non-autistic adults (M = 51 years, SD = 15.33) about a range of negative life experiences, including violence.…”
Section: Rates Of Interpersonal Violencementioning
confidence: 89%
“…The reported rates appear substantially -and alarmingly -high compared to the general population where prevalence of violence ranges between 35 to 40% (Australian Bureau of Statistics, 2016;World Health Organisation, 2013). Only two studies that collected self-report data from both autistic and non-autistic groups found no difference in rates of reported interpersonal violence (Gibbs et al, 2021;Libster et al, 2023). It is important to note, however, that in the Gibbs et al (2021) study the mean age of autistic and non-autistic participants was 43 years, and the time frame was restricted to the previous two years only.…”
Section: Prevalence Of Interpersonal Violencementioning
confidence: 92%
See 2 more Smart Citations
“…Research has shown that autistic individuals are more likely to experience victimization (Pfeffer, 2016), inclusive of sexual victimization (Edelson, 2010; Libster et al, 2023; Rothman et al, 2023) than others. Yet, the body of work that has empirically examined autistic individuals’ vulnerability to victimization, in general, has largely focused on autistic children (Pfeffer, 2016) or has been limited by small sample sizes (Weiss & Fardella, 2018).…”
Section: Disabilities: Autismmentioning
confidence: 99%